Benefits and risks of antiplatelet therapy for moyamoya disease: a systematic review and meta-analysis - Liu, Tingting; Qin, Mingzhen; Xiong, Xuejiao; Li, Tingting; Feng, Luda; Lai, Xinxing; Gao, Ying (Frontiers in Neurology, 2023)
Background Moyamoya disease (MMD) is a leading cause of stroke in children and young adults, whereas no specific drugs are available. Antiplatelet therapy (APT) has been considered a promising treatment option, but its effectiveness remains controversial. Therefore, we aimed to comprehensively evaluate the benefits and risks of APT for MMD. Methods We systematically searched PubMed, Embase, and Cochrane Library electronic databases from their inception to 30 June 2022 and conducted a systematic review. All-cause mortality was taken as the primary outcome. Results Nine studies that enrolled 16,186 patients with MMD were included. The results from a single study showed that APT was associated with lower mortality [hazard ratio (HR) = 0.60; 95% confidence interval (CI) (0.50–0.71); p < 0.01] and improved bypass patency after surgical revascularization [HR = 1.57; 95% CI (1.106–2.235); p < 0.05]. The results of the meta-analysis showed that APT reduced the risk of hemorrhagic stroke [HR = 0.47; 95% CI (0.24–0.94); p < 0.05] but neither reduced the risk of ischemic stroke [HR = 0.80; 95% CI (0.33–1.94); p = 0.63] nor increased the proportion of independent patients [RR = 1.02; 95% CI (0.97–1.06); p = 0.47]. Conclusion Current evidence showed that APT was associated with a reduced risk of hemorrhagic stroke in MMD patients but did not reduce the risk of ischemic stroke or increase the proportion of independent patients. There was insufficient evidence about the benefit of APT on survival and postoperative bypass patency after surgical revascularization. However, the results should be interpreted cautiously because of the limited number of studies. Systematic review registration https://www.crd.york.ac.uk/prospero/.